Masochizmy. Mitologizacja jako estetyka kryzysu w twórczości Brunona Schulza - Augsburger, Janis (Wydawnictwo Naukowe UAM, 2011)
The study Masochisms. Mythologizing as an Aesthetics of Crisis in the Work of Bruno Schulz, parts of which have been translated below, presents the thesis that in the work of B. Schulz the phenomenon of mythologizing is connected with masochism – a concept conceived of as a historical, cultural and aesthetic interpretative category. The combination of the two phenomena makes it possible to notice some relationships between Schulz’s literary and graphic works which have not been recognized yet. The author discusses some psychoanalytical, sociological, historical and philosophical notions of masochism applicable to a literary text. She tries to describe the “masochistic aesthetics” appearing in Schulz’s short stories (on the narrative level: lack of motion, suspense, tension) and in his graphics (theatricalization, lack of eye contact between the figures) and shows how this aesthetics integrates the prose of Schulz, his Idolatrous Book and his illustrations for the short story The Book.
Masochisms. Mythologizing as an Aesthetics of Crisis in the Work of Bruno Schulz